THE ROLE OF COFFEE AND TEA EXPORTS IN DRIVING REGIONAL ECONOMIC GROWTH: A QUANTITATIVE ANALYSIS - Nita Rachmanisa Hanifa; Dika Djatnika (Branding: Jurnal Manajemen dan Bisnis, 2023)
This study endeavors to meticulously scrutinize the causal relationship between the exportation of coffee and tea and the dynamics of the Bandung Regency's GRDP. Employing a quantitative research approach, the study leverages a comprehensive documentation method. Its analytical framework hinges on secondary data, specifically time-series data spanning from 2018 to 2022. These invaluable data sources are culled from official reports furnished by the Bandung Regency Department of Trade and Industry, the West Java Provincial Department of Trade and Industry, Plantation Company Associations, the Central Statistics Agency (BPS) of the Bandung Regency, and the Central Statistics Agency (BPS) of West Java. The methodological cornerstone of this study is the utilization of multiple regression analysis, a robust tool for dissecting intricate relationships. The empirical results, derived from rigorous statistical testing, illuminate noteworthy insights. Specifically, the t-test outcomes underscore the salience of the impact of coffee exports on the GRDP. The calculated significance value (Sig.) of 0.003, well below the conventional significance threshold of 0.05, indicates a robust, positive, and statistically significant influence of coffee exports on the GRDP. Equally compelling is the analogous analysis applied to tea exports. Here, the significance value (Sig.) of 0.000, likewise below the 0.05 threshold, signifies a potent, positive, and statistically significant effect of tea exports on the GRDP. Of paramount significance is the application of the F-test, providing a holistic evaluation of the combined influence of coffee and tea exports on GRDP. The calculated F-value (410883.205) convincingly surpasses the tabulated F-value (6.94), cementing the inference that coffee and tea exports jointly exert a substantive, positive, and statistically significant impact on GRDP. The plantation sector emerges as an indispensable driver of economic expansion in the Bandung Regency.